2016
DOI: 10.1111/jan.13056
|View full text |Cite
|
Sign up to set email alerts
|

The first year: the support needs of parents caring for a child with an intellectual disability

Abstract: This study informs health professionals about how to provide holistic, timely support to parents of children with intellectual disabilities in the first year of life. There is an urgent need to review how nurses and midwives can provide relevant support that is responsive to parents' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
(126 reference statements)
1
12
0
3
Order By: Relevance
“…The larger study identified several facets of support need for parents caring for infants with an intellectual disability (Douglas et al., ). The results presented here represent detail of the analysis of parents’ information needs specifically, which emerged as a significant factor for parents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The larger study identified several facets of support need for parents caring for infants with an intellectual disability (Douglas et al., ). The results presented here represent detail of the analysis of parents’ information needs specifically, which emerged as a significant factor for parents.…”
Section: Resultsmentioning
confidence: 99%
“…The larger study identified several facets of support need for parents caring for infants with an intellectual disability (Douglas et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As fathers are less likely to utilize non-profit support or advice organizations (Skotko et al 2011), the role for health professionals, as the frequent first port of call for fathers seeking support and information is particularly crucial. Although there have been several key studies exploring parent's experiences of having a child with a disability (Douglas et al 2016;Pelchat et al 2003), this study stands out for two particular reasons. Firstly, it focused on Down syndrome.…”
Section: Basic Theme: Reactions Of Health Professionals To Their Childmentioning
confidence: 99%